2018
DOI: 10.1038/s41598-018-29054-w
|View full text |Cite
|
Sign up to set email alerts
|

The urinary microbiome associated with bladder cancer

Abstract: Recent findings suggest that human microbiome can influence the development of cancer, but the role of microorganisms in bladder cancer pathogenesis has not been explored yet. The aim of this study was to characterize and compare the urinary microbiome of bladder cancer patients with those of healthy controls. Bacterial communities present in urine specimens collected from 12 male patients diagnosed with bladder cancer, and from 11 healthy, age-matched individuals were analysed using 16S sequencing. Our result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
178
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(197 citation statements)
references
References 57 publications
14
178
1
4
Order By: Relevance
“…20,21 In bladder cancer research, using urine specimens, one study observed increased richness of microbiota diversity in bladder cancer patients, whereas no significant differences in microbial diversity were observed in a different evaluation. 10,22 Based on our findings, we hypothesize that the loss of microbiota diversity may be related to the incidence of bladder cancer. As previously shown in the gut, the balance between specific microbial groups may be more relevant than overall urine composition.…”
Section: Discussionmentioning
confidence: 72%
“…20,21 In bladder cancer research, using urine specimens, one study observed increased richness of microbiota diversity in bladder cancer patients, whereas no significant differences in microbial diversity were observed in a different evaluation. 10,22 Based on our findings, we hypothesize that the loss of microbiota diversity may be related to the incidence of bladder cancer. As previously shown in the gut, the balance between specific microbial groups may be more relevant than overall urine composition.…”
Section: Discussionmentioning
confidence: 72%
“…While these techniques have been used extensively to study the urinary microbiome as it pertains to benign urological disease states, only a small number of studies to date have investigated the role of the urinary microbiome in bladder cancer [4,5]. Unfortunately, all published studies in this domain have been limited by their use of voided urine, which increases the potential for introduction of urethral and peri-urethral contamination into patient samples.…”
mentioning
confidence: 99%
“…Another urine sample contained a high Lactobacillus abundance, which has previously been shown to be abundant in urine samples (40). In addition, presence of Atopobium , Gardnerella , Campylobacter , Prevotella and Anaerococcus point towards an existing urinary microbiota (41). However, Pseudomonas , a common Zymo kit contaminant, was still found in this urine sample, and for Magna more than 25% of reads could not be classified (Fig S3C).…”
Section: Resultsmentioning
confidence: 99%